PENGARUH EXPERIENTIAL LEARNING KOLB MELALUI KEGIATAN PRAKTIKUM TERHADAP HASIL BELAJAR BIOLOGI SISWA - Suryani, Suryani; Rudyatmi, Ely; Pribadi, Tyas Agung (Journal of Biology Education, 2014)
Abstract _____________________________________________________________The aim of researchwas determine the application of kolbs experiential learning model through practical activity improve students biology learning outcomes in plant tissue structure and function material in SMAN 1 Ngawen. This research was quasi-experimental which used nonequivalent control group design. The population was all science students grade XI (1, 2, and 3). The samples were taken purposively (students of XI-IPA1 as control and XI-IPA2 as experimental). The datawere increasing student learning outcomes, student opinion, and teacher opinion.Increasing student learning outcomes have been determined by N-gain, whereasdifferent of learning outcomes based on t-test.Teacher andstudentopinion were determined by questionnaire and interview.Increasing student learning outcomes was high in experimental class 57%, whereas 25% in control. Average of student learning outcomes in experimental class 83,92, whereas 75,99 in control. Result t-test average of student learning outcomes between experimental classwith control showed tcount> ttable, it was 4,05 > 1,67. It means there was significant difference. Teacher and student opinionto the learning activity had Â good. Conclusion of research was application of kolbs experiential learning model through practical activity improve students biology learning outcomes in plant tissue structure and function material in SMAN 1 Ngawen. Abstrak _____________________________________________________________ Tujuan penelitian ini untuk mengetahui apakah penerapan model experiential learning kolb melalui kegiatan praktikum meningkatkan hasil belajar biologi siswa materi struktur dan fungsi jaringan tumbuhan di SMA Negeri 1 Ngawen. Penelitian ini merupakan penelitian quasi-experimental dengan desain nonequivalent control group design. Populasi penelitian ini adalah seluruh siswa kelas XI-IPA (1, 2, dan 3). Sampel ditentukan secarapurposive sampling (siswa kelas XI-IPA1 sebagai kontrol danXI-IPA2 sebagai eksperimen). Data penelitian berupa peningkatan hasil belajar siswa, tanggapan siswa, dan tanggapan guru. Peningkatan hasil belajar siswa ditentukan denganN-gain, sedangkan perbedaan hasil belajar berdasarkan uji t. Tanggapan siswa dan guru ditentukan menggunakan angket dan wawancara. Peningkatan hasil belajar siswa yang tinggi pada kelas eksperimen 57%, sedangkan kontrol 25%. Rata-rata hasil belajar siswa kelas eksperimen 83,92, sedangkan kontrol 75,99. Hasil uji t rata-rata hasil belajar siswa antarakelas eksperimen dengan kontrolmenunjukkan nilai thitung> ttabel, yaitu 4,05 > 1,67.Artinya ada perbedaan yang signifikan. Tanggapan siswa dan guru terhadap penerapan pembelajaran baik. Simpulan penelitian ini adalah penerapan model experiential learning kolb melalui kegiatan praktikum meningkatkan hasil belajar biologi siswa materi struktur dan fungsi jaringan tumbuhan di SMA Negeri 1 Ngawen. Â  Â